Essential quality parameters of commercial virgin coconut oil - Dayrit, Fabian M (Archīum Ateneo, 2007)
Chemical analyses conducted on commercial samples of virgin coconut oil (VCO) produced by four different methods gave the following ranges of values: % Fatty acid composition: C6: 0.24 to 0.49%; C8: 4.15 to 8.30%; C10: 4.27 to 5.75%; C12: 46.0 to 52.6%; C14: 16.0 to 19.7%; C16: 7.65 to 10.1%; C18: 2.86 to 4.63%; C18:1: 5.93 to 8.53%; C18:2: 1.00 to 2.16%; %moisture by Karl Fischer: 0.05 to 0.12%; %matter volatile at 120 0C: 0.12 to 0.18%; %free fatty acids as lauric acid: 0.042 to 0.329%; and peroxide value: none detected to 1.40. The tests for %moisture by Karl Fischer and %matter volatile at 120 0C can be used to differentiate VCO from and refined, bleached and deodorized coconut oil (RBD CNO). No trans-fatty acid was detected in both VCO and RBD CNO down to 0.01% (w/w) detection limit.